"Connecting Mind to Pen, to Eyes, to Face, to Arms and Legs": Toward a Performative and Decolonial Teaching Practice. (September 2020) - Flockemann, Miki
Abstract : The push to sustain online learning platforms that have been established in the wake of Covid-19 at South African universities raises a number of concerns. Apart from highlighting the stark and ongoing social inequities in terms of access, the need to ensure that there is still scope in our teaching practice for affective and performative encounters has also been thrown into sharp relief. I draw on two teaching contexts, the one dealing with a literary text, and the other a live performance in order to explore the decolonial potential of affective encounters. In addition to illustrating the complex and unpredictable workings of affect in teaching contexts, I also hope to show how these two incidents offer insight into the interface between sensorial and cognitive knowledge in relation to both literary and performance texts. The aim is to demonstrate how student responses to affective encounters resonate with, rather than directly address, some of the "everyday" processes of decoloniality.